Literacy at a Distance in Multilingual Contexts: Issues and Challenges - Ofulue, Christine I. (International Review of Research in Open and Distributed Learning, 2011)
Literacy is perhaps the most fundamental skill required for effective participation in education (formal and non-formal) for national development. At the same time, the choice of language for literacy is a complex issue in multilingual societies like Nigeria. This paper examines the issues involved, namely language policy, language and teacher development, and the role of distance education and information and communication technologies (ICTs), in making literacy accessible in as many languages as possible. Two distance learning literacy projects are presented as case studies and the lessons learned are discussed. The findings of this study suggest that although there is evidence of growing accessibility to ICTs like mobile phones, their use and success to increase access to literacy in the users’ languages are yet to be attained and maximised. The implication of the lessons learned should be relevant to other multilingual nations that seek the goal of increasing access to learning and promoting development so as to harvest economic benefits.